Clinical Outcomes and Frequency of Electroencephalographic Abnormalities in Patients with First Unprovoked Seizure in a Tertiary Care Hospital: A Cross-Sectional Study: Electroencephalographic Findings in Seizure - Masood, Rabbiyah; Malik, Madiha; Rana, Maimoona Tanwir; Habib, Samrat; Nawaz, Ali; Habib, Taha (Pakistan Journal of Health Sciences, 2025)
Epilepsy is a common medical condition that has widespread neurobiological, cognitive, psychological, and social consequences. Recurrent seizures are a common feature of this illness. Individuals experiencing their first unprovoked seizure generally present with Electroencephalographic (EEG) abnormalities, which might reflect a broad range of underlying neurophysiological changes. Identifying and measuring these abnormalities is critical for differentiating between epileptic and non-epileptic seizures, determining suitable treatment techniques, and predicting future seizure risk. Objective: To determine the frequency of abnormal EEG in patients presenting after first unprovoked seizures. Early detection of these abnormalities will better guide for better management and to predict recurrence. Methods: The study was a six-month cross-sectional retrospective held at the Punjab Institute of Neurosciences, Lahore, Pakistan from January 2024 to June 2024. This study employed the non-probability consecutive sampling method. The study included 95 patients who met the inclusion and exclusion criteria. Previous medical data included a complete patient history, clinical examination, and EEG results. Data were then analyzed using SPSS version 21.0. Results: Out of 95 patients, 52.63% were male and 47.37% were female, averaging 52.6 + 5.6 years. A total of 46 individuals (48.42%) had abnormal EEG irrespective of age, gender, length of symptoms, and awareness of symptoms. Conclusion: This study concluded that EEG abnormalities are highly frequent among individuals following their first unprovoked seizure.